Until our blood is dry - Habianic, Kit (Cardigan Parthian Books, 2014)
'Until our Blood is Dry' is a novel of passion and love, betrayal and decisions in a time and place when people were forced to fight for their future during the 1984 coalminers' strike. Nofel am gariad ac angerdd, brad a dewisiadau anodd wedi ei gosod yn ystod streic y glowyr yn 1984, lle mae pobl yn gorfod ymladd am eu dyfodol. Up ahead, Helen saw the police line harden into a barricade of bodies and shields. Resin batons thudded on Perspex shields; slow, thuggish, brutal. Goosebumps studded her arms and legs. Her pace slowed to the truncheons beat. Mary halted a yard from the riot shields, raised her megaphone. We are women from Ystrad an from all over Wales, she said. We are here to make peaceful protest. Here in solidarity with the men. The drumming quickened. Trouble is brewing in Ystrad. It is time to defend jobs, the pits and a way of life that has formed both the life of valley and the nation. The union is squaring up to the Coal Board, the government, the country. Gwyn Pritchard, overman at Blackthorn colliery, believes that the way to save his pit is to keep the mine open and production high. His men disagree and when an old collier dies on Gwyns shift, the mens simmering resentment spills over into open defiance. But Gwyn faces a challenge at home too. His daughter Helen is in love with a fiery young collier, Scrapper Jones. In March 1984, when miners across the country begin the long strike, Scrapper throws himself into the struggle and Helen joins the women, preparing food for the soup kitchen and standing with the men on the picket line. Helen and Gwyn must decide which side they are on as the year-long dispute drives the Pritchard family apart and the Jones family to ruin. What matters most: to be right, to be loved or to belong? Until our Blood is Dry is a novel of passion and love, betrayal and decisions in a time and a place when a people were forced to fight for their future.
Keywords: Coal Strike, Great Britain, 1984-1985 -- Fiction; Strikes and lockouts -- Coal mining -- Wales -- Fiction; Wales -- Social conditions -- 20th century -- Fiction